Study on the differences of fat deposition in cattle-yak and yak based on transcriptomics and metabolomics - Xiong, Lin; Pei, Jie; Wang, Xingdong; Guo, Shaoke; Cao, Mengli; Ding, Zhiqiang; Kang, Yandong; Wu, Xiaoyun; Ge, Qianyun; Guo, Xian (Frontiers in Veterinary Science, 2025)
The hybridization of yak with cattle is an effective means to improve the yak’s production performance. The fatty trait greatly affects the meat quality, the growth and development, and the reproduction of bovine. In this study, the thickness of subcutaneous fat in cattle-yaks and yaks was measured, and fatty acid composition was detected by a gas chromatograph-mass spectrometer (GC-MS); the transcriptome and metabolome in fat were detected by mRNA-Sequencing (mRNA-Seq) and an ultra-high performance liquid chromatography-mass spectrometry technique (UHPLC-MS/MS), respectively. The results revealed that the thickness of subcutaneous fat in yaks was greater than the value in cattle-yaks; the content of saturated fatty acids (SFAs), polyunsaturated fatty acids (PUFAs), and Σn-3 PUFAs in cattle-yaks’ fat were higher than the values in yaks’ fat, whereas the unsaturated fatty acids (UFAs) and monounsaturated fatty acids (MUFAs) content in cattle-yaks’ fat were lower. Furthermore, the expression of the SREBF1 gene in the fat deposition of the two bovines was affected by PI3K-Akt and AMPK signal pathways, which led to the expression change of downstream VLDLR, INSIG1, ACACA, LIPE, SLC2A4, CPT1C, SCD, and DGAT2 genes. Therefore, fatty acid synthesis, glucose and lipid transport, and lipid synthesis differed in fat depositions between the two bovines, ultimately leading to differences in the fat quantity in the two bovines. Moreover, the expression of VLDLR, CPT1C, LEP, SCD, and CEBPE genes was closely related to the differences in fatty acid composition between the fat tissues of two bovines. The results can provide some theoretical basis for yak breeding and can also promote the improvement of yak production.